2012
DOI: 10.1097/bcr.0b013e31823359c4
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injuries Requiring Hospitalization for Infants Younger Than 1 Year

Abstract: To investigate burn injuries requiring hospitalization sustained during the first year of life, clinical data collected during hospital treatment of infants younger than 1 year were reviewed. The principal aim was to chart the etiology and mechanism of burn injuries in this group to focus on the necessary preventive measures. The authors also review literature focusing especially on children younger than 1 year. Patients identified in the electronic database were referred to the Hospital for Children and Adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…Yet, in the current study, in the youngest age group, less than 6 months, the incidence of burn injuries was higher in girls. Our previous work on inhospital-treated burn victims aged less than 1 year from a single center revealed that girls outnumbered boys by 1.5 to 1 [1], and in the present report we confirmed that this phenomenon is national and characteristic of Finland. Burn injuries in this age cohort take place while the infant is held in the arms of a caregiver who at the same time is holding a hot item, such as cup of tea or coffee [1,2].…”
Section: Discussionsupporting
confidence: 94%
“…Yet, in the current study, in the youngest age group, less than 6 months, the incidence of burn injuries was higher in girls. Our previous work on inhospital-treated burn victims aged less than 1 year from a single center revealed that girls outnumbered boys by 1.5 to 1 [1], and in the present report we confirmed that this phenomenon is national and characteristic of Finland. Burn injuries in this age cohort take place while the infant is held in the arms of a caregiver who at the same time is holding a hot item, such as cup of tea or coffee [1,2].…”
Section: Discussionsupporting
confidence: 94%
“… 3 , 4 Limited data is available on infant burns, worldwide. 5 There is a scarcity of published data on infant burns from Saudi Arabia. The aim of this study is to identify the epidemiology, pattern, outcome, and impact of infant burns in eastern Saudi Arabia.…”
mentioning
confidence: 99%
“…Cognizant mobilization develops literally step-by-step; first by creeping and crawling, later aspiring to an upright position by standing, and finally walking. Children's natural curiosity and urge to explore their environment sets them at risk for injuries in general, and burns in particular [18,24,25,35]. The proportion of burn patients less than 1 year of age, is 18% of all the burn victims at the Children's Hospital in Helsinki, and on a national scale the number of burned children aged less than 1 year has increased during recent years [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…Children's natural curiosity and urge to explore their environment sets them at risk for injuries in general, and burns in particular [18,24,25,35]. The proportion of burn patients less than 1 year of age, is 18% of all the burn victims at the Children's Hospital in Helsinki, and on a national scale the number of burned children aged less than 1 year has increased during recent years [24,25]. The American Burn Association database, which presents the 10-year cumulative experience from several burn centers, shows that the number of burns in children under 1 year seen at hospitals has increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation